The Utility of Modified Wells Score as a Pre-Test Risk Stratification Tool in Suspected Cases of Pulmonary Embolism Undergoing Computed Tomography Pulmonary Angiogram - Nisar, Uzma; Nasir, Hina; Malik, Zaha Iqbal; Bangash, Madiha; Amin, Zafar; Palwa, Abdur Rahim (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To assess the validity of pre-test evaluation of patients with Modified Wells score at our facility to improve diagnostic yield of CT pulmonary angiography for pulmonary embolism.Study Design: Prospective longitudinal study.Place and Duration: Department of Computed Tomography, Armed Forces Institute of Radiology & Imaging, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Feb to Jul 2019.Methodology: After approval from the Ethical Review Board, 60 patients with clinical suspicion of pulmonary embolism were selected. Modified Wells score was calculated for each patient, and a senior consultant reviewed their CT Pulmonary Angiograms.Results: Sixty patients were assessed from February to July 2019. Pulmonary embolism was diagnosed in 21(35%) patients; 22(37%) patients were unremarkable, while alternate diagnosis was provided for 17(28%) patients. Modified Wells score was 66.6% sensitive and 74.3% specific for diagnosis of pulmonary embolism, with a positive predictive value of 58.3% and a negative predictive value of 80.5%.Conclusion: Modified Wells score carries a good negative predictive value for ruling out pulmonary embolism. Hospitals must devise their departmental protocol utilizing risk stratification tools, lab tests and other safer imaging alternatives, where applicable.